Teknik pengukuran untuk meningkatkan koefisien konsistensi perilaku=Technique of Measu,ement for Increasing Coefficient of Behavior Consistemcy - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
This study examined the technique of measurement for increasing the coefficient of behavior consistency. This technique measures behavior on various situations and accasions. The results of measurement are averaged over an increasing number of events. The means of subjects' scores on all odd days are correlated with the mean of subjects' scores on all even days. Compared with the correlation between any two single days, it is hipothesized that the coefficient of correlation between these two means will be higher. Twenty five high school students have been requested to fill-out self-evaluation scale measuring their behavior and their behavior intention. Subjects were asked to fill-out the scale each day in the afternoon for 16 days. The results of the study confirm the hypothesis.